Molecular landscape of esophageal cancer: implications for early detection and personalized therapy. Issue 1 (19th June 2018) - Talukdar, Fazlur Rahman; di Pietro, Massimiliano; Secrier, Maria; Moehler, Markus; Goepfert, Katrin; Lima, Sheila Soares Coelho; Pinto, Luis Felipe Ribeiro; Hendricks, Denver; Parker, Mohamed Iqbal; Herceg, Zdenko
Abstract: Esophageal cancer (EC) is one of the most lethal cancers and a public health concern worldwide, owing to late diagnosis and lack of efficient treatment. Esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) are main histopathological subtypes of EC that show striking differences in geographical distribution, possibly due to differences in exposure to risk factors and lifestyles. ESCC and EAC are distinct diseases in terms of cell of origin, epidemiology, and molecular architecture of tumor cells. Past efforts aimed at translating potential molecular candidates into clinical practice proved to be challenging, underscoring the need for identifying novel candidates for early diagnosis and therapy of EC. Several major international efforts have brought about important advances in identifying molecular landscapes of ESCC and EAC toward understanding molecular mechanisms and critical molecular events driving the progression and pathological features of the disease. In our review, we summarize recent advances in the areas of genomics and epigenomics of ESCC and EAC, their mutational signatures and immunotherapy. We also discuss implications of recent advances in characterizing the genome and epigenome of EC for the discovery of diagnostic/prognostic biomarkers and development of new targets for personalized treatment and prevention. Abstract : Esophageal cancer (EC) is one of the most lethal cancers and a public health concern worldwide, owing to late diagnosis and lack of efficient treatment. Esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) are main histopathological subtypes of EC that show striking differences in geographical distribution, possibly due to differences in exposure to risk factors and lifestyles. In this review, we summarize recent advances in the areas of genomics and epigenomics of ESCC and EAC, their mutational signatures and immunotherapy. We also discuss implications of recent advances in characterizing the genome and epigenome of EC for the discovery of diagnostic/prognostic biomarkers and development of new targets for personalized treatment and prevention.